2014
DOI: 10.1089/fpd.2014.1812
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks Associated with Cantaloupe, Watermelon, and Honeydew in the United States, 1973–2011

Abstract: Fresh fruits and vegetables are an important part of a healthy diet. Melons have been associated with enteric infections. We reviewed outbreaks reported to the Centers for Disease Control and Prevention’s Foodborne Disease Outbreak Surveillance System during 1973–2011 in which the implicated food was a single melon type. We also reviewed published literature and records obtained from investigating agencies. During 1973–2011, 34 outbreaks caused by a single melon type were reported, resulting in 3602 illnesses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
77
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 19 publications
0
77
0
1
Order By: Relevance
“…Since cluster analysis is a multivariate data analysis techniquehence, it requires continuous variables as inputs-it is necessary to first obtain some measurements of the characteristics of each sanitizer in the form of a continuous variable. In a regression analysis of the type (6) adjusted to the whole data from a given sanitizer, the parameter estimates ␤ 0 , ␤ 1 , ␤ 2 , and ␤ 3 can be thought of as the continuous variables characterizing the disinfectant capacity of the sanitizer. This is because for a sanitizer, the higher the intercept ␤ 0 (representing the mean log reduction R at the mean log concentration C, the mean temperature T, and the mean time t), the higher the microbial mean log reduction R. Similarly, a sanitizer with higher slopes ␤ 1 , ␤ 2 , and ␤ 3 will produce a greater mean log reduction R for a given log concentration C, temperature T, and time t, respectively.…”
Section: Meta-analysis Of Sanitization In Produce Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Since cluster analysis is a multivariate data analysis techniquehence, it requires continuous variables as inputs-it is necessary to first obtain some measurements of the characteristics of each sanitizer in the form of a continuous variable. In a regression analysis of the type (6) adjusted to the whole data from a given sanitizer, the parameter estimates ␤ 0 , ␤ 1 , ␤ 2 , and ␤ 3 can be thought of as the continuous variables characterizing the disinfectant capacity of the sanitizer. This is because for a sanitizer, the higher the intercept ␤ 0 (representing the mean log reduction R at the mean log concentration C, the mean temperature T, and the mean time t), the higher the microbial mean log reduction R. Similarly, a sanitizer with higher slopes ␤ 1 , ␤ 2 , and ␤ 3 will produce a greater mean log reduction R for a given log concentration C, temperature T, and time t, respectively.…”
Section: Meta-analysis Of Sanitization In Produce Processingmentioning
confidence: 99%
“…One of the chief concerns related to the safety of these products is their recurrent and increased association with disease outbreaks (3)(4)(5)(6). Epidemiological investigations indicate that Salmonella, pathogenic Escherichia coli, and Listeria monocytogenes stand out as the most important bacterial agents linked to fresh-produce disease outbreaks (3,(5)(6)(7). Recent studies have reported the occurrence and high diversity of these microorganisms in the environment or in close areas of produce farming areas (8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cases of foodborne illness and illness outbreaks caused by Salmonella and other pathogenic bacteria, associated with consumption of fruits and vegetables from both domestic and imported sources, have increased over the last two decades (Bowen, Fry, Richards, & Beuchat, 2006; Centers for Disease Control & Prevention (CDC), 2013; USFDA, 2003a). Specifically, during 1973–2011, 19 illness outbreaks caused by the consumption of cantaloupes were reported, resulting in 1,012 illnesses and 215 hospitalizations (Walsh, Bennett, Mahovic, & Gould, 2014). Most of the outbreaks have been linked to poor or inappropriate cleaning and sanitation at the packing houses.…”
Section: Introductionmentioning
confidence: 99%
“…have been implicated in many outbreaks of foodborne illness linked to the consumption of fresh fruits, including cantaloupe melons. And, several serotypes of Salmonella have been responsible for multi‐state illness outbreaks and other illness cases associated with consumption of cantaloupe (Richards & Beuchat, 2004; Walsh et al, 2014). Because Salmonella can attach to rough surfaces and build biofilm complexes, these organisms can be hard to remove using just chlorine and tap water.…”
Section: Introductionmentioning
confidence: 99%